3D learning spaces and activities fostering users’ learning, acceptance, and creativity - Shin, Donghee; Park, Seyoung (Journal of computing in higher education, 2019)
As an instructional material, 3D instructions afford people to learn procedural-manipulative tasks. Observing and emulating motions presented in 3D animations is important in learning contexts. This study examined the effects of visual cueing in an effort to identify the optimal way to present information in a 3D virtual environment. While previous studies have found that animations are more effective than static images for learning procedural-manipulative tasks, the transient nature of dynamic visualizations might create an unnecessary cognitive load on learners. To compensate strategically for the lack of permanency, this study suggests combining dynamic and static visualizations into one medium by adding transparent static images (visual cueing) to an animation. A between-subjects experiment was conducted to examine the effects of visual cueing on cognitive load and learning outcomes. The study found that the hybrid of dynamic and static visualizations was beneficial for reducing cognitive load, although it did not improve learning outcomes. The results suggest a design strategy for improving the effectiveness of 3D instructional animations. The findings are broadly applicable to numerous learning contexts, such as virtual reality storytelling, augmented reality games, and diverse gamification services.